Effect of Nanoparticles and Surfactant on Phase Inversion of Two Phases - Farhan, Nada M. (Iraqi Journal of Chemical and Petroleum Engineering, 2017)
In the present study, a pressure drop technique was used to identify the phase inversion point of oil-in-water to water-in-oil flows through a horizontal pipe and to study the effect of additives (nanoparticles, cationic surfactant and blend  nanoparticles-surfactant) on the critical dispersed volume fraction (phase inversion point). The measurements were carried  for mixture velocity ranges from 0.8 m/sec to 2.3 m/sec. The results showed that at low mixture velocity 0.8 and 1 m/sec there is no effect of additives and velocity on phase inversion point, while at high mixture velocities the phase inversion point for nanoparticles and blend (nanoparticles/surfactant) systems was delayed (postponed) to a higher value of the dispersed phase volume fraction (oil volume fraction) compared to the system of surfactant where the phase inversion point was occurred at low dispersion phase volume fraction.For all systems the desperation volume fraction at the point of inversion decreases with increasing mixture velocity.Indeed, the results showed that surfactant was more effective on phase inversion point than solid nanoparticles.